Development of Green Village Based on Processing of Vegetable Flour Products in Sindon Village, Boyolali District - Kurnia, Pramudya; Rauf, Rusdin; muhtadi, muhtadi; Suranto, Suranto (Muhammadiyah University Press, 2020)
Sindon Village is one of the vegetable center villages in Boyolali district. Vegetable production in the village is quite abundant, but there has not been optimal flour processing practice. The purpose of this community service activity is to improve community skills in processing flour-based vegetable products prepared for commercialization. The partners of the community service activities consisted of 3 groups, namely PKK, women farmer groups (KWT) and Aisyiyah groups. The activity begins with training in making cookies products with the addition of spinach flour. Then a spinach flour-based product processing competition was conducted. The results of the activity showed that the three partner groups were skilled at practicing the process of making spinach cookies. In the product competition, each partner group has featured its fine products. The result of the competition is the identification of flour-based vegetable products that will be continued in the commercialization process.